Hypogammaglobulinemia and Poor Performance Status are Predisposing Factors for Vancomycin-Resistant Enterococcus Colonization in Patients with Hematological Malignancies - Ümit, Elif Gülsüm (Turk J Haematol, 2017)
OBJECTIVE: Vancomycin-resistant enterococci (VRE) are common pathogens of hospital-acquired infection. Long hospitalization periods, use of broad-spectrum antibiotics, and immunosuppression are major risks for VRE colonization. We aimed to evaluate patients’ characteristics and factors that may contribute to VRE colonization. MATERIALS AND METHODS: Data of 66 patients with colonization and 112 patients without colonization who were hospitalized in the hematology clinic were collected. Hematological malignancies, preexisting gastrointestinal complaints, the presence of hypogammaglobulinemia at the time of diagnosis, complications like neutropenic enterocolitis (NEC), and Eastern Cooperative Oncology Group (ECOG) and Karnofsky performance statuses were recorded. RESULTS: Ages of the patients ranged between 19 and 95 years (mean: 55.99). Karnofsky and ECOG scores were statistically related to VRE colonization (p<0.000 and p<0.000), though only the Karnofsky score was significant based on logistic regression analysis. Almost all patients with acute leukemia (45 patients) had been on antibiotics (piperacillin-tazobactam, ceftazidime, and meropenem), while no patients with myelodysplastic syndrome, myeloma, or benign diseases and 2 patients with lymphoma and 1 with chronic myeloid leukemia were on antibiotics. Median time for colonization regardless of antibiotic use and diagnosis was 4.5 days (range: 3-11 days). In the VRE-colonized group, 40.9% of patients had NEC development, while in the non-colonized group, only 1.7% had NEC development. In the VRE-colonized group 46 patients (69.7%) and in the non-colonized group 27 patients (24.1%) had hypogammaglobulinemia at diagnosis; among these patients, 23 patients in the VRE-colonized group (50%) had a B-cell malignancy (lymphoma, myeloma, or chronic lymphocytic leukemia). CONCLUSION: Besides already anticipated diseases like leukemia, B-cell malignancies are also at high risk for colonization. This proclivity may be attributed to lack of gastrointestinal IgA due to hypogammaglobulinemia. Prolonged hospitalization (>7 days) may also be accepted as a risk factor, independent of diagnosis or antibiotic use. Performance status is also an important factor for colonization, which may be related to poorer hygiene and increased external help.